The impact of guessing word meanings through context on vocabulary acquisition of students in Vo Van Kiet high school, Kien Giang - Huỳnh Thị Sánh (Trường Đại học Trà Vinh, 2020)
The primary goal of this study is to investigate the effects of guessing word meanings from context in vocabulary learning on seventh-grade students’ vocabulary acquisition at VVK High school. The second aim is to explore students’ attitudes towards the use of guessing word meanings from context for their vocabulary acquisition.